2021
DOI: 10.1093/molbev/msab340
|View full text |Cite
|
Sign up to set email alerts
|

Island Biogeography Revisited: Museomics Reveals Affinities of Shelf Island Birds Determined by Bathymetry and Paleo-Rivers, Not by Distance to Mainland

Abstract: Island biogeography is one of the most powerful subdisciplines of ecology: its mathematical predictions that island size and distance to mainland determine diversity have withstood the test of time. A key question is whether these predictions follow at a population-genomic level. Using rigorous ancient-DNA protocols, we retrieved ∼1000 genomic markers from ∼100 historic specimens of two Southeast Asian songbird complexes from across the Sunda Shelf archipelago collected 1893–1957. We show that the genetic affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…As studies incorporating hDNA become increasingly common (Colella et al, 2020;Toussaint et al, 2021c;Garg et al, 2022), researchers will be faced with decisions regarding sample selection. Should an ethanol-preserved specimen always be extracted if a museum specimen is available?…”
Section: Sample Preservation and Sequence Capture Successmentioning
confidence: 99%
“…As studies incorporating hDNA become increasingly common (Colella et al, 2020;Toussaint et al, 2021c;Garg et al, 2022), researchers will be faced with decisions regarding sample selection. Should an ethanol-preserved specimen always be extracted if a museum specimen is available?…”
Section: Sample Preservation and Sequence Capture Successmentioning
confidence: 99%
“…On the other hand, many islands separated by deep‐sea channels have never been physically connected to the continent, yet may host dispersal‐limited species, suggesting a role for overseas dispersal (Cowie & Holland, 2006; Salvi et al, 2021). Therefore, the genetic composition of island populations has been shaped by island‐specific features and species traits, such as spatial isolation, time‐since‐isolation and dispersal capacity (Garg et al, 2022; Heaney et al, 2005; Roberts, 2006; Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of degraded samples from natural history collections has been useful for determining the phylogenetic placement (Delling et al, 2023) and biogeography (Garg et al, 2022) of poorly known or extinct lineages. In this study, we phylogenetically place five genera and six species for the first time, each of which are known from only a few voucher specimens, and use these results to formulate hypotheses regarding homalopsid evolution.…”
Section: Museum Genomics Of Homalopsidaementioning
confidence: 99%
“…The sea-level fluctuations of this region are often cited as a driver of speciation and population structure in invertebrates and vertebrates (Li & Li, 2018;Wu et al, 2022;Wüster et al, 2005). However, recent geological studies that better identify the dates of land bridges (Husson et al, 2020;Sarr et al, 2019) suggest that current hypotheses must be revisited to test if newly identified processes in other taxa also affect diversification and dispersal scenarios (Garg et al, 2022;Sholihah et al, 2021).…”
mentioning
confidence: 99%